Activation-Induced FoxP3 Expression Regulates Cytokine Production in Conventional T Cells Stimulated with Autologous Dendritic Cells - Cavatorta, Derek J. (American Society for Microbiology, 2012)
A defining feature of dendritic cells (DCs) is their ability to induce the proliferation of autologous T cells in the absence of foreign antigen—a process termed the “autologous mixed leukocyte reaction” (AMLR). We report that equine monocyte-derived DCs, but not macrophages, are potent inducers of the AMLR. The response is contact dependent and major histocompatibility complex class II dependent and primarily involves CD3(+) CD4(+) CD8(−) T cells. Upon stimulation with DCs or the mitogen concanavalin A, a subset of the proliferating T cells expresses the regulatory T-cell (Treg) transcription factor FoxP3. Although many of these FoxP3(+) T cells are capable of producing the effector cytokines interleukin-4 (IL-4) and gamma interferon (IFN-γ), they are more likely to produce IL-10 and less likely to produce IFN-γ than equivalent FoxP3(−) cells. Therefore, FoxP3 expression is an inherent component of equine T cell activation and is associated with a more immunosuppressive cytokine profile. These results confirm that FoxP3 expression in the horse, in contrast to the mouse, is regulated similarly to FOXP3 expression in humans and provide evidence that FoxP3 expression by conventional T cells may help regulate the developing immune response.